Examining coaching practices and philosophy through the lens of organizational culture in a Danish high-performance swimming environment - Junggren, S. E.; Elbæk, L.; Stambulova, N. B. (International Journal of Sports Science & Coaching, 2018)
Interest in coaching and coaches, as well as coach-athlete relationships, has for a long time been a traditional and solid part of talent development literature. In recent times, talent development research has employed a holistic ecological approach and emphasized the important role of a broader athletic environment in athletes` development and a constitutive role of organizational culture in the success of such an environment. This case study uses the holistic ecological perspective to examine coaching practices and philosophy through the lens of organizational culture in a Danish high-performance swimming environment. The environment was selected based on its performance success but also because of its nontraditional organization compared to typical Danish swimming clubs. Data were generated from in-depth interviews with six coaches, 30 h of participant observation of training and meetings, and analysis of related documents. Thematic data analysis was guided by Schein`s model of organizational culture. The findings revealed the organizational culture that incorporates specific features of coaching practices and philosophy through cultural artifacts, espoused values, and basic assumptions. In the artifacts, coaching practices were explicit (e.g. flexible training groups and schedules) and philosophy implicit (e.g. ongoing flow of feedback), while in the espoused values, coaching philosophy was explicit (e.g. swimmers as whole persons, long-term development focus) and consistent with basic cultural assumptions (e.g. swimmers` autonomy as a basis for progress). The study revealed that the cultural lens was helpful in exploring consistency between what coaches communicate about what they do (and how and why they do it) and what they actually did (and how they did it).